The Sacrament of the Eucharist - Laurance, John D., 1938- (Book collections on Project MUSE., 2012)
In The Sacrament of the Eucharist, the latest volume in the Lex Orandi Series, John D. Laurance considers the Eucharist by way of two questions: How, by his first-century life, death, and resurrection, does Jesus Christ save all human beings throughout history from eternal death and make possible their permanent union with God? How is that salvation made available now through the community of the church in her liturgical celebrations? Soteriology and ecclesiology therefore play a prominent role in Laurance's investigation. After forging a theology of the liturgy primarily out of the work of Rahner, Kilmartin, and Chauvet, the author investigates the nature of the lex ordandi, lex credendi relationship and offers guidelines on how best to read the church's faith in her life of prayer. He then uses both steps to discover the faith meaning of a particular Eucharist as typically celebrated in a modern American parish on Sunday morning.